Mechanical stretch upregulates connexin43 in human trabecular meshwork cells. (20th March 2019) - Tellios, Nikoleta; Feng, Mary; Chen, Nancy; Liu, Hong; Tellios, Vasiliki; Wang, Mary; Li, Xiangji; Chang, Caitlin A.; Hutnik, Cindy
Abstract: Background: Primary open angle glaucoma (POAG) patients have hallmark increases in intraocular pressure (IOP) and noted dysfunction of the trabecular meshwork (TM). Connexin43 (Cx43) is a gap junction widely expressed on the TM that is important for intercellular communication. The human gene is known as gap junction alpha‐1 (GJA1). Since the role of Cx43 in the TM is not fully understood, we set out to determine the effect of excess mechanical stretch on cultured human trabecular meshwork cells (hTMCs) and to specifically investigate the effect of stretch on Cx43 expression and function. Methods: Primary hTMCs were cultured and subjected to 48 hours of 15% cyclic mechanical stretch at a frequency of 1 Hz. Levels of apoptosis and necrosis secondary to stretch were investigated using colorimetric assays. The effect of stretch on gap junction Cx43 and GJA1 was investigated by RT‐PCR, immunoblotting and immunofluorescence. The migration of Lucifer Yellow dye was used to assess intercellular communication. Results: Stretch significantly increased the rates of apoptosis and necrosis in hTMCs. The increased rate of injury in stretched hTMCs was further associated with significant upregulation of GJA1 mRNA and Cx43 protein. Upregulation of Cx43 protein was concomitant to increased intercellular communication. Conclusions: We have shown stretch to increase GJA1 gene and Cx43 protein expression, as well as intercellular communication. We have further shown stretch to be injurious to hTMCs. Upregulation of Cx43 in the hTM subsequent to stretch is a novel finding, which may be useful in elucidating the mechanism of TM injury in POAG patients.